Desarrollo de la producción oral del idioma inglés a partir de la utilización de técnicas interactivas en los estudiantes de décimo año de educación básica en la Unidad Educativa “Álvaro Valladares” en la ciudad del Puyo durante el período 2015-2016. - Zuñiga Jara, Maria Victoria (2017)
The present research deals with oral production from the use of interactive techniques, since oral production is a skill that uses language, it is usually limited by the contest in which it is learned. The present study aimed to develop the oral production of the English language in the students of the Tenth year of Basic Education of die Educational Unit "Alvaro Valiadares" in die city of Puyo during the period 2015-2016, worked with 2S students in two Times indistintos, from the implementation of a didactic guide based on interactive techniques. In accordance with the above. research instruments such as the interview and the observation guide were used to diagnose students academic results before and after the application of these techniques. The applied methodology was a qualitative-quantitative design, the inductive-deductive method was used, due to its field application and quasi-experimental character, the final result allowed to group the work developed with these students in a product that is called Interactive Guide For Speaking Skill. This guide served as an instrument that provides activities for the development of oral expression skills* allowing students to learn new meanings and interact among them, as well as to promote the exchange of information in real life situations in a foreign language, in this language. If English